Characteristics of Corrosion Related to Ash Deposition on Boiler Heating Surface during Cofiring of Coal and Biomass - Yongzheng Wang; Yu Sun; Lei Jiang; Lu Liu; Yungang Li (Journal of Chemistry)
In order to investigate the regularity and mechanism of corrosion related to ash deposition on the boiler heating surface during cofiring of coal and biomass, the influence of fuel property, type of metal tubes (heating surface), proportion of blended biomass, and atmosphere in the furnace was studied by using the static corrosion mass gain method with the high-temperature tube furnace system. The results indicated that the effect of biomass property on ash corrosion is greater than that of coal, which was mainly due to high content of alkali metals and chlorine in biomass fuels. The corrosion resistance of metal pipes is T91 > 12CrMoVG > 20G. T91 is the most appropriate one, and it can effectively inhibit chlorine corrosion and can be used as the ideal material for the biomass-fired boiler and the biomass and coal cofired boiler. In addition, ash deposition can significantly aggravate the corrosion of metal tubes, and the degree of corrosion tends to become significant with increasing proportion of blended biomass fuels. HCl can aggravate metal corrosion, which can be inhibited by SO2.